(untitled) (Revista Sistemas de Producción Agroecológicos, 2012)
In a commercial farm of Villavicencio, Meta, to 800 meters of altitude, with a temperature between 18 and 24ºC and relative humidity of 85%, 140 pigs were finished, 40 in system of cement floor and 100 in system of deep bedding, housed in two cement floor corrals and four deep bedding corrals, distributed at random in a design of blocks with two treatments, deep bedding and cement floor, and two repetitions, using husk of rice as bed. The productive parameters of the two systems were averaged and adjusted to 105 days of permanency to after to be analyzed them comparatively. They were not differences (P>0,05) in food conversion neither in daily gain of weight among the two valued systems. They were deference (P<0,05) in intake food daily. It was presented a mortality of 4 and 0% for deep bedding and cement floor, respectively; although the animals housed in system of deep bedding had a bigger incidence of pathologies, deep bedding was 1% more profitable that cement floor, for production and sale of compost, additionally deep bedding had a better handling of residuals and at a smaller cost.